A Model of the Deformations of a Cross‐Section of the Spinal Cord Due to Periodic Pressure Loadings - Harris, Paul J.; Venton, Jenny (Mathematical methods in the applied sciences, 2025)
ABSTRACT Changes in the pressure of the cerebrospinal fluid that surrounds the spinal cord can cause deformations of the spinal cord, which, in turn, may lead to the cord being damaged. In addition, the changes in the pressure of the surrounding cerebrospinal fluid can cause changes to the pressure of the extracellular fluid which saturates the spinal cord. The finite element method can be used to solve the differential equations, which describe both how the cord deforms and changes in the pressure of the extracellular fluid but often this requires a large number of time‐steps to obtain an accurate and stable numerical solution. We present an alternative approach that uses a Fourier series method that avoids the need for using a time‐stepping scheme and that can model how a pressure pulse affects the spinal cord.